Everyone Wants to Speak English: The Struggles of an American Study-Abroad Student in Japan - Hiromi Tobaru (Japanese Language and Literature)
This case study examines an American undergraduate student’s study abroad (SA) experience in Japan, focusing on his self-perceived interactional experiences. Despite achieving notable success in language acquisition and developing social networks during his SA period, the student viewed his experience in the context of academic language learning—specifically, learning Japanese—as a failure due to his predominant use of English. This study explores the gap between the student’s experience and perception through quantitative and qualitative analysis of the student’s language use. Quantitative analysis revealed that overall, the student used Japanese more frequently than English, but most of his interactions outside the classroom involved either English or a combination of English and Japanese. Qualitative analysis uncovered the student’s struggle in reconciling the locals’ preference for English conversations with his own desire to use Japanese when interacting with Japanese local people. The results also indicate that the student encountered challenges in effectively using English as a global language, illustrating the complexity of navigating intercultural interactions. These findings suggest that the global dominance of English impacts and, at times, complicates the language-learning experiences of Anglophone SA students in Japan.